Readability of online patient education materials for parents after a failed newborn hearing screen. (October 2019) - Sax, Leah; Razak, Alina; Shetty, Kunal; Cohen, Michael; Levi, Jessica
Abstract: Objective: A cross-sectional study design was utilized to evaluate the readability of patient education materials on the newborn hearing screen from Google and major institutions. Methods: The top 55 websites from the Google search "failed newborn hearing screen" and websites from major institutions (the U.S. News & World Report ranked top 10 children's hospitals, the top 5 pediatric otolaryngology fellowships as ranked by Doximity Residency Navigator, the Centers for Disease and Control, the American Academy of Pediatrics and the American Academy of Otolaryngology–Head and Neck Surgery) were compiled. Text from each website was edited to remove extraneous text. Readability grade was calculated using the Flesch-Kincaid Grade Level (FKGL), Flesch Reading Ease Score, Gunning-Fog Index (GFI), Simple Measure of Gobbledygook (SMOG), Coleman-Liau Index, and Automated Readability Index. Intra- and inter-observer reliability were assessed. Results: 26 websites from Google and 29 websites from major institutions were evaluated. From Google, provider-oriented websites (n = 2) were more difficult to read than patient-oriented websites (n = 24) with statistical significance for FKGL (p < 0.001), GFI (p < 0.013) and SMOG (p < 0.001). From the major institutions, more than half were at a reading level that exceeded the average American adult with an average FKGL 9.71 ± 2.69. Intra- and inter-observer reliability were both excellent with an intra-class correlation coefficient for each readability tool ≥0.950 (p < 0.001). Conclusion: Online patient education materials about the newborn hearing screen may be too difficult for the average reader. Revisions to these materials and redirection to more readable online resources may be necessary to benefit a more inclusive patient population.